IDH1/IDH2 Inhibition in Acute Myeloid Leukemia - Cerchione, Claudio; Romano, Alessandra; Daver, Naval; DiNardo, Courtney; Jabbour, Elias Joseph; Konopleva, Marina; Ravandi-Kashani, Farhad; Kadia, Tapan; Martelli, Maria Paola; Isidori, Alessandro; Martinelli, Giovanni; Kantarjian, Hagop (Frontiers in Oncology, 2021)
Recently, the discovery of biological and clinical properties of mutated isoforms 1 and 2 mutations of isocitrate dehydrogenases (IDH) 1 and 2, affecting approximately 20% of patients with acute myeloid leukemia (AML), lead to the development of an individualized treatment strategy. Promoting differentiation and maturation of the malignant clone targeting IDH is an emerging strategy to promote clinical responses in AML. Phase I/II trials have shown evidence of safety, tolerability, and encouraging evidence of efficacy of two small molecule inhibitors targeting IDH2 and IDH1 gene mutations, respectively enasidenib and ivosidenib. In this review, the contribution of IDH1/IDH2 mutations in leukemogenesis and progress of targeted therapeutics in AML will be highlighted.